Transformation of health law: Legal protection for persons with mental disorders - Fani, Veranika Santiani; Sara, Rineke (International Journal Labs, 2024)
The legal protection for individuals with mental disorders in Indonesia is governed by various laws; however, there are still significant challenges in their implementation. This research uses a normative juridical method to analyze and study existing laws and regulations, focusing on their application in the legal protection of individuals with mentally disorders. The research aims to provide a thorough analysis that highlights existing regulations and reflects the practical realities, ultimately offering relevant recommendations to improve the legal system and mental health policies in Indonesia. The results indicate that despite having a robust legal framework, the challenges in its application indicate the need for transformation and improvement of the health law system in Indonesia so that the protection of individual rights can be more optimal and sustainable. In addition, healthcare professionals, including doctors, nurses, and counselors, need to receive specialized training on sensitive approaches to mental health so they can provide better and more humane care for patients with mental disorder. Additionally, despite the efforts and regulations that have been established, the implementation of mental health laws and policies has not yet demonstrated the expected effectiveness. This work provides valuable insights for policymakers, practitioners, and advocates, ultimately advancing the legal discourse surrounding mental health in Indonesia, laying the groundwork for future research and enriching legal scholarship.